2002
DOI: 10.1007/s00438-002-0710-5
|View full text |Cite
|
Sign up to set email alerts
|

Poly(A) site choice during mRNA 3′-end formation in the Schizosaccharomyces pombe wos2 gene

Abstract: In the fission yeast Schizosaccharomyces pombe, the wos2 gene encodes p23, a highly conserved protein which functions as a co-chaperone for the heat shock protein Hsp90. This p23 protein binds to Hsp90, but its activities and regulatory mechanisms are still unclear. Northern analysis has shown that the wos2 gene produces three transcripts of about 1.1, 0.9 and 0.8 kb, which are expressed differentially depending on the growth temperature. The largest and the smallest transcripts were most abundant at 25 degree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 22 publications
2
3
0
Order By: Relevance
“…Further investigation revealed that 1) temperature-sensitive mmi1 mutations activate 3′ RNA processing and splicing of crs1 in nonmeiotic cells, and 2) the decision to retain the newly synthesized RNA in the nucleus for destruction rather than to process and export it is mediated by a bipartite regulatory element consisting of a DSR and a noncanonical polyadenylation signal (McPheeters et al ., 2009). The cotranscriptional regulatory mechanism proposed for crs1 is consistent with the current view that splicing and other RNA processing reactions, which were traditionally designated “posttranscriptional” events, are in fact coupled to RNA synthesis in vivo (reviewed in Perales and Bentley, 2009). In this study, we surveyed gene expression parameters and the impact of mutations in RNA surveillance factors for a diverse array of meiotic genes to assess the contributions of known control mechanisms as well as to potentially uncover new ones.…”
Section: Introductionsupporting
confidence: 74%
See 1 more Smart Citation
“…Further investigation revealed that 1) temperature-sensitive mmi1 mutations activate 3′ RNA processing and splicing of crs1 in nonmeiotic cells, and 2) the decision to retain the newly synthesized RNA in the nucleus for destruction rather than to process and export it is mediated by a bipartite regulatory element consisting of a DSR and a noncanonical polyadenylation signal (McPheeters et al ., 2009). The cotranscriptional regulatory mechanism proposed for crs1 is consistent with the current view that splicing and other RNA processing reactions, which were traditionally designated “posttranscriptional” events, are in fact coupled to RNA synthesis in vivo (reviewed in Perales and Bentley, 2009). In this study, we surveyed gene expression parameters and the impact of mutations in RNA surveillance factors for a diverse array of meiotic genes to assess the contributions of known control mechanisms as well as to potentially uncover new ones.…”
Section: Introductionsupporting
confidence: 74%
“…As discussed in all four sections below, our results highlight the importance of events once believed to occur post-transcriptionally but that are now known to be initiated while transcript synthesis is still ongoing (reviewed in Perales and Bentley, 2009). …”
Section: Discussionsupporting
confidence: 56%
“…The involvement of Pfs2 in crs1 regulation suggests a link to control mechanisms discovered in more complex eukaryotes, as putative orthologues of this protein (CstF-50 paralogues) have been implicated in the regulation of Arabidopsis flowering55 and display increased expression during mouse spermatogenesis56. A key difference, however, is that previous studies of regulated 3′ processing, including two (non-meiotic) examples in S. pombe 20,57-59 described switching between sites rather than the differential activation implied by our data (Fig. 2a).…”
Section: Discussionmentioning
confidence: 99%
“…Besides, it is important to mention that the polyadenylation mechanism is regulated through different ways: the correct positioning of the sequence elements present in the 3 end, and their nucleotide composition [6,33] and structural environment [34][35][36][37][38]; the recruitment of polyadenylation factors in promoter regions [33,39] and their concentration [40][41][42]; the RNAP II elongation speed [43]; the presence of structured regions (Aux-DSEs, local chromatin conformation, presence of nucleosomes and epigenetic marks) [6,44]; the concentration of transcriptional elongation factors [6,45,46]; the existence of RNA binding proteins [33]; the presence of splicing factors [47][48][49][50][51]; and the activation of specific signaling pathways [52,53].…”
Section: Eukaryotic Mrna 3 End Processingmentioning
confidence: 99%
“…Additionally, the importance of the pre-mRNA structure in the polyadenylation event of eukaryotic genes, mainly transcripts of yeasts, plants, humans, and other mammals, has also been demonstrated. For example, studies in murine secretory IgM concluded that a stem structure promoted the recognition of a DSE by the CstF [34], and findings in Schizosaccharomyces pombe demonstrated the existence of an association between the thermal stability of the RNA structure and the preferential use of specific PASes [35]. Another research mentioned that the Aux-DSE was a polyadenylation stimulating factor, since it was determined that approximately 30% of 244 human pre-mRNAs analyzed contained G-rich downstream auxiliary elements capable of forming G-quadruplex structures [44].…”
Section: Bioinformatic Prediction Of Rna Structurementioning
confidence: 99%